Skin lesions in envenoming by cnidarians (Portuguese man-of-war and jellyfish): etiology and severity of accidents on the Brazilian coast - Haddad Junior, Vidal [UNESP]; Silveira, Fábio Lang Da; Migotto, Álvaro Esteves (Instituto de Medicina Tropical, 2010)
This work attempts to establish dermatological identification patterns for Brazilian cnidarian species and a probable correlation with envenoming severity. In an observational prospective study, one hundred and twenty-eight patients from the North Coast region of São Paulo State, Brazil were seen between 2002 and 2008. About 80% of these showed only local effects (erythema, edema, and pain) with small, less than 20 cm, oval or round skin marks and impressions from small tentacles. Approximately 20% of the victims had long, more than 20 cm, linear and crossed marks with frequent systemic phenomena, such as malaise, vomiting, dyspnea, and tachycardia. The former is compatible with the common hydromedusa from Southeast and Southern Brazil (Olindias sambaquiensis). The long linear marks with intense pain and systemic phenomena are compatible with envenoming by the box jellyfish Tamoya haplonema and Chiropsalmus quadrumanus and the hydrozoan Portuguese man-of-war (Physalis physalis). There was an association between skin marks and probable accident etiology. This simple observation rule can be indicative of severity, as the Cubozoa Class (box jellyfish) and Portuguese man-of-war cause the most severe accidents. In such cases, medical attention, including intensive care, is important, as the systemic manifestations can be associated with death.

Cnidários são animais que apresentam no corpo (especialmente nos tentáculos) organelas de defesa chamadas nematocistos, podendo causar graves envenenamentos. Este trabalho procura estabelecer padrões clínicos auxiliares na identificação das espécies de cnidários brasileiros e pesquisar provável correlação das lesões na pele com a gravidade do acidente. Cento e vinte e oito pacientes foram observados no Pronto-Socorro de Ubatuba (Litoral Norte do estado de São Paulo) em período de seis anos (2002-2008). Cerca de 80% dos acidentes mostraram apenas manifestações locais (dor, eritema e edema). Nestes casos, as marcas cutâneas foram pequenas, ovais e arredondadas, algumas vezes com impressões de pequenos tentáculos. As marcas foram menores que 20 cm. Aproximadamente 20% das vítimas tinham lesões longas, lineares e cruzadas, maiores que 20 cm com frequente observação de fenômenos sistêmicos, como mal estar, vômitos, dispnéia e taquicardia. O padrão das marcas arredondadas e curtas é compatível com hidromedusa muito comum nas regiões Sudeste e Sul do Brasil (Olindia sambaquiensis), que causa acidentes de pequena magnitude. As marcas longas e lineares, associadas à dor intensa e fenômenos sistêmicos, são compatíveis com envenenamento pelas cubomedusas Tamoya haplonema e Chiropsalmus quadrumanus e o hidrozoário Physalis physalis, a caravela. Houve associação entre as marcas cutâneas e a provável etiologia do acidente. Esta regra simples de observação clínica pode ter valor clínico, uma vez que a Classe Cubozoa (vespas-do-mar) e as caravelas causam os acidentes mais graves. Nestes casos, a atenção médica deve ser redobrada, incluindo cuidados intensivos, uma vez que fenômenos sistêmicos podem se associar a óbitos.
Lesões dermatológicas observadas nos acidentes por cnidários (águas-vivas e caravelas): etiologia e gravidade dos envenenamentos no litoral do Brazil
Keywords: Cnidarians; Box jellyfish; Portuguese man-of-war; Human envenoming; Skin marks; Brazil